Gamma-aminobutyric acid and glutamate/glutamine levels in the dentate nucleus and periaqueductal gray with episodic and chronic migraine: a proton magnetic resonance spectroscopy study - Wei Wang; Xueyan Zhang; Xiaoyan Bai; Yingkui Zhang; Ziyu Yuan; Hefei Tang; Zhiye Li; Zhangxuan Hu; Yaqing Zhang; Xueying Yu; Binbin Sui; Yonggang Wang (The Journal of Headache and Pain, 2022)
Abstract Background The pathogenesis of migraine chronification remains unclear. Functional and structural magnetic resonance imaging studies have shown impaired functional and structural alterations in the brains of patients with chronic migraine. The cerebellum and periaqueductal gray (PAG) play pivotal roles in the neural circuits of pain conduction and analgesia in migraine. However, few neurotransmitter metabolism studies of these migraine-associated regions have been performed. To explore the pathogenesis of migraine chronification, we measured gamma-aminobutyric acid (GABA) and glutamate/glutamine (Glx) levels in the dentate nucleus (DN) and PAG of patients with episodic and chronic migraine and healthy subjects. Methods Using the MEGA-PRESS sequence and a 3-Tesla magnetic resonance scanner (Signa Premier; GE Healthcare, Chicago, IL, USA), we obtained DN and PAG metabolite concentrations from patients with episodic migraine (n = 25), those with chronic migraine (n = 24), and age-matched and sex-matched healthy subjects (n = 16). Patients with chronic migraine were further divided into those with (n = 12) and without (n = 12) medication overuse headache. All scans were performed at the Beijing Tiantan Hospital, Capital Medical University. Results We found that patients with chronic migraine had significantly lower levels of GABA/water (p = 0.011) and GABA/creatine (Cr) (p = 0.026) in the DN and higher levels of Glx/water (p = 0.049) in the PAG than healthy controls. In all patients with migraine, higher GABA levels in the PAG were significantly associated with poorer sleep quality (GABA/water: r = 0.515, p = 0.017, n = 21; GABA/Cr: r = 0.522, p = 0.015, n = 21). Additionally, a lower Glx/Cr ratio in the DN may be associated with more severe migraine disability (r = -0.425, p = 0.055, n = 20), and lower GABA/water (r = -0.424, p = 0.062, n = 20) and Glx/Water (r = -0.452, p = 0.045, n = 20) may be associated with poorer sleep quality. Conclusions Neurochemical levels in the DN and PAG may provide evidence of the pathological mechanisms of migraine chronification. Correlations between migraine characteristics and neurochemical levels revealed the pathological mechanisms of the relevant characteristics.